ANALISIS STRATEGI PROBLEM-BASED LEARNING DENGAN HASIL BELAJAR PADA MEKANIKA TEKNIK - Dian Safitri (EDUCATIONAL JOURNAL : General and Specific Research, 2024)
This article explores the importance of integrating the Problem-Based Learning (PBL) model in the context of building engineering education, with a focus on the engineering mechanics field. PBL is a learning approach that challenges students to solve complex problems, providing benefits such as the enhancement of essential problem-solving skills and improved academic performance. Research suggests that implementing PBL methods has been successful in enhancing student achievement across various disciplines, including engineering mechanics. The findings indicate that the use of PBL has a significant positive effect on student learning outcomes, with the extent of impact influenced by factors such as student-teacher interaction, learning environment, and student motivation. Furthermore, the study highlights the effectiveness of PBL in enhancing students' problem-solving abilities. Therefore, the article concludes that the adoption of PBL can be a valuable learning strategy for improving student performance in the field of building engineering, particularly within the realm of engineering mechanics.